Robert McRuer on Crip Theory - CP-assistenten (2016)
Interview of Robert McRuer on crip theory.
Keywords: EDI; approches et analyses; arts; capacitisme; cours; discipline; histoire et politique; premier cycle; ressource en ligne; santé; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Sex and disability - McRuer, Robert; Mollow, Anna (Duke University Press, 2012)
The title of this collection of essays, Sex and Disability, unites two terms that the popular imagination often regards as incongruous. The major texts in sexuality studies, including queer theory, rarely mention disability, and foundational texts in disability studies do not discuss sex in much detail. What if'sex'and'disability'were understood as intimately related concepts? And what if disabled people were seen as both subjects and objects of a range of erotic desires and practices? These are among the questions that this collection's contributors engage. From multiple perspectives—including literary analysis, ethnography, and autobiography—they consider how sex and disability come together and how disabled people negotiate sex and sexual identities in ableist and heteronormative culture. Queering disability studies, while also expanding the purview of queer and sexuality studies, these essays shake up notions about who and what is sexy and sexualizable, what counts as sex, and what desire is. At the same time, they challenge conceptions of disability in the dominant culture, queer studies, and disability studies.Contributors. Chris Bell, Michael Davidson, Lennard J. Davis, Michel Desjardins, Lezlie Frye, Rachael Groner, Kristen Harmon, Michelle Jarman, Alison Kafer, Riva Lehrer, Nicole Markotić, Robert McRuer, Anna Mollow, Rachel O'Connell, Russell Shuttleworth, David Serlin, Tobin Siebers, Abby L. Wilkerson
Keywords: approches et analyses; arts; autobiographie; capacitisme; cours; discipline; ethnographie; premier cycle; queer; ressource en ligne; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Ecrire comme vivre: dans l'hybridite: entretien avec Anne-Marie Alonzo - Dupre, Louise (Voix et Images, 1994)
Keywords: EDI; amériques; approches et analyses; arts; canada; capacitisme; cours; discipline; lit2815; lit3495; premier cycle; québec; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires